Long-range proximity effect in Nb-based heterostructures induced by a magnetically inhomogeneous permalloy layer. (20th February 2017) - Cirillo, C; Voltan, S; Ilyina, E A; Hernández, J M; García-Santiago, A; Aarts, J; Attanasio, C
Abstract: Odd-frequency triplet Cooper pairs are believed to be the carriers of long-range superconducting correlations in ferromagnets. Such triplet pairs are generated by an inhomogeneous magnetism at the interface between a superconductor (S) and a ferromagnet (F). So far, reproducible long-range effects were reported only in complex layered structures designed to provide the magnetic inhomogeneity. Here we show that spin triplet pair formation can be found in simple unstructured Nb/permalloy ( Py = Ni 0.8 Fe 0.2 )/Nb trilayers and Nb/Py bilayers, but only when the thickness of the ferromagnetic layer ranges between 140 and 250 nm. The effect is related to the emergence of an intrinsically inhomogeneous magnetic state, which is a precursor of the well-known stripe regime in Py that in our samples sets in at thickness larger than 300 nm.